2021
DOI: 10.3390/genes12020252
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Diversity despite Conserved Karyotype Organization in the Giant Trahiras from Genus Hoplias (Characiformes, Erythrinidae)

Abstract: In the fish genus Hoplias, two major general groups can be found, one of which is formed by the “common trahiras” (Hoplias malabaricus group) and the other by the “giant trahiras” (Hoplias lacerdae group, in addition to Hoplias aimara), which usually comprises specimens of larger body size. Previous investigations from the giant trahiras group recovered 2n = 50 meta/submetacentric chromosomes and no sex chromosome differentiation, indicating a probable conservative pattern for their karyotype organization. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…In addition, many macrochromosomes and microchromosomes displayed higher conspecific signals in the CGH experiment, suggesting that the two species have diverged in their centromeric repeat sequences. Our observation is consistent with other studies in birds ( Ellegren et al, 2012 ), as well as other taxa ( Haaf and Willard, 1997 ; Bensasson et al, 2008 ; Pertile et al, 2009 ; de Sassi et al, 2021 ; Oliveira et al, 2021 ), showing fast evolution of centromeric sequences. For example, comparison of the whole genome sequences of two closely related species of Ficedula flycatchers, which also belong to the Muscicapidae family, revealed that the centromeres were among the most differentiated regions of the genome between the species ( Ellegren et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, many macrochromosomes and microchromosomes displayed higher conspecific signals in the CGH experiment, suggesting that the two species have diverged in their centromeric repeat sequences. Our observation is consistent with other studies in birds ( Ellegren et al, 2012 ), as well as other taxa ( Haaf and Willard, 1997 ; Bensasson et al, 2008 ; Pertile et al, 2009 ; de Sassi et al, 2021 ; Oliveira et al, 2021 ), showing fast evolution of centromeric sequences. For example, comparison of the whole genome sequences of two closely related species of Ficedula flycatchers, which also belong to the Muscicapidae family, revealed that the centromeres were among the most differentiated regions of the genome between the species ( Ellegren et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…The development and improvement of large-scale genotyping-by-sequencing (GBS) procedures allowed high-resolution analysis using Single Nucleotide Polymorphisms (SNPs) for genetic diversity studies in non-model organisms ( Steane et al, 2011 ; Yang et al, 2013 ; Sánchez-Sevilla et al, 2015 ; Alkimin et al, 2018 ; Souza et al, 2019 ; Oliveira et al, 2020 ; Sassi et al, 2021 ). Combining such genomic and cytogenetic data for pairs of species/populations in which there are variations related to geographic distribution, analysis of chromosomal rearrangements, and sex chromosome systems provide a critical tool to understanding the role of these events to generate biodiversity.…”
Section: Introductionmentioning
confidence: 99%